Molecular Characterization of Mungbean Yellow Mosaic Disease and Coat Protein Gene in Mungbean Varieties of Bangladesh - Islam, Mohammad Nurul; Sony, Sonia Khan; Borna, Rita Sarah (Plant Tissue Culture and Biotechnology, 2012)
Mungben yellow mosaic virus (MYMV), a member of the genus begomovirus causing major yield loss of mungbean. Development of MYMV tolerant/resistant varieties using an antiviral strategy may be one of the potential options to overcome MYMV diseases. In the present investigation, molecular identification of yellow mosaic disease and characterization of (MYMV) coat protein (CP) gene was attempted. Yellow mosaic symptomatic samples were identified through PCR using conserved region primers designed after alignment of the available CP sequences in NCBI data base. Sequence analysis of the PCR amplified samples showed 97% sequence similarities with the coat protein gene of Mungbean Yellow Mosaic India Virus (MYMIV) Bangladesh strain and was designated as MYMIV-BD. This appears to be the first report of the molecular identification of MYMV in Bangladesh. DOI: http://dx.doi.org/10.3329/ptcb.v22i1.11263 Plant Tissue Cult. & Biotech. 22(1): 73-81, 2012 (June)